ROME STATUTE OF INTERNATIONAL CRIMINAL COURT AND LEGAL STATUS OF THE RUSSIAN FEDERATION - I. I. Sinyakin; E. A. Kopylova (Московский журнал международного права, 2018)
Introduction. This article examines the legal consequences attached to the Russia’s notification of its intention not to become a party to the ICC. The authors point out the confusing language employed by Russian Ministry for Foreign Affairs in its attendant declarations and highlight the necessity to strictly stick to legal terminology especially in documents and speeches intended as a message to foreign States. These materials express the official position of the Russian Federation and need to be unequivocal and not subject to interpretation. Otherwise, a State taking liberty with terminology in its official declarations takes a risk of assuming in the eyes of international community obligations that it did not intend to assume. The authors’ remarks may be used in the future interactions with the ICC and generally in similar situations.Materials and methods. The article uses treaties, declarations of States and doctrinal research on the law of treaties. The authors rely on various methods to reach their conclusions, among which treaty interpretation is most frequently used.Research results. In the article the authors show that on 16 November 2016, Russia disclosed its intention not to become a party to the 1998 Rome Statute of the International Criminal Court. The Ministry for Foreign Affairs stressed that although fighting against impunity, including collectively through international tribunals, is of the utmost importance to Russia, in its view, the ICC has not lived up to the expectations held at the Rome diplomatic conference. The Ministry pointed out the disproportionality between the finances spent by the Court in fourteen years of work and only four verdicts rendered. It also indicated understanding the decision of several States-parties to initiate proceedings to withdraw from the Statute.Discussion and conclusions. In this article the authors draw attention to potential adverse effect of such declarations and notifications on the legal status of the Russian Federation. The article concludes that no substantial changes have affected the status of the Russian Federation as a result of its decision not to become a party to the Rome Statute. Russian officials simply have had recourse to common language to express a legal concept thereby creating a confusion and distorting the reality.